$W^{3,p}$ Estimate of Degenerate Complex Monge-Ampère Equations (Journal of Mathematical Study, 2025)
Degenerate complex Monge-Ampère equations arise naturally in the study of geometry of singular varieties. In this paper, we prove gradient estimate and $W^{3,p}$ estimate for a class of degenerate complex Monge-Ampère equations.
Keywords: Complex Monge-Ampère equations; Kähler manifolds